Band Engineering and Structural-Geometrical Engineering in 2D/3D van der Waals Heterostructures for Advanced Photodetection and Intelligent Sensing - Yang, Miaomiao; Gong, Kaiwen; Cui, Yanxia; Liu, Shaoding; Li, Guohui; Lin, Shenghuang (Nano-Micro Letters, 2026)
With the rapid advancement of the information era, the demand for device integration and intelligent sensing has grown significantly. Traditional three-dimensional (3D) materials are constrained by lattice mismatch and interfacial defects, and their limited functionalities often require bulky auxiliary components. In contrast, the rich family of two-dimensional (2D) materials eliminates lattice-matching constraints and offers unique light-matter interactions, paving the way for compact and novel intelligent sensing technologies. However, large-area fabrication and precise layer alignment in all-2D systems remain major challenges that hinder device scalability. Given that the performance and manufacturing capabilities of 2D materials cannot replace traditional semiconductors (such as Si), they are more likely to be heterogeneously integrated with conventional 3D semiconductors. 2D/3D heterojunctions combine the distinctive optoelectronic properties of 2D materials with the mature electronic functionalities of 3D semiconductors. In this work, we present recent advances in 2D/3D heterojunction photodetectors, with a particular emphasis on the underlying physical mechanisms, including band structure design, interface optimization, external-field coupling, and novel topological configurations. Meanwhile, we also explore emerging opportunities for CMOS-compatible and intelligent sensing optoelectronic systems. Finally, the challenges and future research directions toward the integrated development of 2D/3D heterojunctions are discussed. Highlights: 1 This review illustrates the application potential of 2D/3D systems from the perspectives of device fabrication, device performance, and system integration. 2 This review examines implementation strategies for high-performance and intelligent 2D/3D heterojunction photodetectors, including band modulation, interface engineering, electric-field coupling, and geometric/structural design. 3 This review provides a comprehensive discussion of the respective advantages and limitations of different modulation strategies.